A study on consumer acceptance of wet noodles added with freshwater mussel flour (anodonta sp) - Sari, Ira; ', Destiawati; ', Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was intended to evaluate the consumer acceptance of wetnoodles added with freshwater mussel flour. Four types of wet noodles wereprepared from a mixture of wheat flour, eggs, salt, water, vinegar, onion, garlic,celery leaves, and backing soda the mixure were asked with freshwater musselflour at a level of 0%, 5%, 10% and 15% of the wheat flour weight. Wet noodleswas evaluated for consumer acceptance, moisture, protein and bacterial count. Theresult showed that wet noodles added with 5% of freshwater mussel flour was themost preperable by consumer. Moisture of wet noodles added with freshwatermussel 0%, 5%, 10% and 15% was 61,59%, 58,67%, 57,73% and 55,42%respectively; protein was 2,46%, 9,06%, 11,72%, 15,03% respectively; andbacterial count was 4,35 x 102 sel/g, 4,3 x 102 sel/g, 3,2 x 102 sel/g and 2,4 x 102sel/g respectively.Keyword: Wet noodles, freshwater mussel, flour, consumer acceptance